Homeschooling como proposta de educação no Brasil : direito ou privilégio? - Rigoni, Larissa Morés (2023)
This dissertation investigates the topic of homeschooling in Brazil. The research focus is on examining whether this educational approach in the country constitutes a right or a privilege. To do so, we analyze the assumptions, the historical context of its origin, research findings, the narratives of the National Association of Homeschooling (ANED), Brazilian laws concerning the matter, as well as the debate in the Brazilian Supreme Federal Court (STF) and its consequences. The objective of this analysis is to identify the inherent weaknesses of homeschooling within the framework of educational policies in the current Brazilian context. This is a basic, exploratory research with a qualitative problem-solving approach, and a theoretical/bibliographic and documentary procedure. It is grounded in an analytical-hermeneutical method, with primary theoretical support from researchers in the field and is structured into five chapters. The first chapter presents aspects related to the research construction, topic delimitation, justification, the guiding research question, general and specific objectives, methodological sampling, and the research framework. The second one explains the origin of homeschooling and its implementation in Brazil, along with an overview of research conducted on the subject in theses and dissertations from 2013 to 2021. It also highlights some cases where families opted for homeschooling, even without current legislation in the country, and provides an analysis of the ANED website, which offers support to families choosing this approach. The third chapter provides a study of the documents governing Brazilian education, such as the 1988 Federal Constitution and the 1996 National Education Guidelines and Framework Law, as well as a critical analysis of bills and already approved documents regarding homeschooling in the country. In the fourth chapter, the analysis and interpretation of the study are presented, aiming to answer more specific research questions on whether education should be considered a right or a privilege when homeschooling is introduced in the country. Finally, in the fifth chapter, it is concluded that Home Education in Brazil is constructed as an educational privilege to the extent that what is a right granted by law to everyone becomes the privilege of a few.